2005
DOI: 10.1124/jpet.105.096719
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Dependent Degradation of p53 Protein Despite Phosphorylation at Its N Terminus by Acetaminophen

Abstract: We previously reported that acetaminophen (APAP, 4-hydroxyacetanilide) caused apoptosis of C6 glioma cells. Therefore, we hypothesized that the level of p53, which usually stimulates apoptosis, might be increased after APAP exposure. However, APAP exposure for 24 h markedly decreased the p53 content and its downstream target p21 in a concentration-dependent manner. Reduction of p53 was not accompanied by a decrease in p53 mRNA in C6 glioma cells, suggesting that p53 was mainly affected at the protein level. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
4
18
2
Order By: Relevance
“…However, induction of phosphorylation of p53 by UV irradiation is still intact. Our observation is similar to that of Lee et al (2006), who observed the reduction of p53 by acetaminophen, but not etoposide and 5 0 FU, despite phosphorylation of p53 on serines 15 and 37 . Furthermore, a recent study has also shown that p16 inactivation leads to increased levels of p53 in human mammary epithelial cells, and that the sustained upregulation of p53 may increase the selective pressure to inactivate p53 (Zhang et al, 2006).…”
Section: Discussionsupporting
confidence: 79%
“…However, induction of phosphorylation of p53 by UV irradiation is still intact. Our observation is similar to that of Lee et al (2006), who observed the reduction of p53 by acetaminophen, but not etoposide and 5 0 FU, despite phosphorylation of p53 on serines 15 and 37 . Furthermore, a recent study has also shown that p16 inactivation leads to increased levels of p53 in human mammary epithelial cells, and that the sustained upregulation of p53 may increase the selective pressure to inactivate p53 (Zhang et al, 2006).…”
Section: Discussionsupporting
confidence: 79%
“…However, the mRNA steady state levels do not correlate with the protein levels and consistently, c-Myc does not bind to Id2 promoter in response to APAP-overdose. Although APAP induces c-myc transcription, it also triggers the proteasome pathway leading to decreased cMyc half life, which is in agreement with other observations showing the APAP-induced degradation of specific proteins [77,78]. On the other hand, it has been shown that c-Myc downregulation is involved in the Id2 repression [34].…”
Section: Gsh Depletion and Id2 Down-regulationsupporting
confidence: 79%
“…When intracellular GSH is depleted by AAP metabolic transformation, DOX undergoes oxidation to a less toxic metabolite. Another possibility is that HAAP, notwithstanding its apoptotic effect to C6 glioma cells, was shown to decrease the level of p53 protein (Lee et al, 2006b). The wild-type p53 is present in HepG2 cells (Lee et al, 2002), and its suppression was found to play a significant role in preventing apoptosis (Sanchez-Prieto et al, 2000;Bai and Cederbaum, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The role of apoptotic pathway during AAP hepatotoxicity remains controversial (Ray and Jena, 2000;Gujral et al, 2002;Jaeschke and Bajt, 2006). Nevertheless, studies of AAP toxicity in hepatoma cell lines, performed in our laboratory and other laboratories, unequivocally indicate the occurrence of apoptosis (Boulares et al, 2002;Manov et al, 2002Manov et al, , 2004Neuman, 2002;Macanas-Pirard et al, 2005;Lee et al, 2006b). Because metabolic activation of AAP is reduced or does not occur in tumor cells, unmetabolized AAP contributes directly to the toxicity, causing apoptosis (Boulares and Ren, 2004).…”
mentioning
confidence: 99%